Inflammasome activation by Gram-positive bacteria: Mechanisms of activation and regulation - Keestra-Gounder, A. Marijke; Nagao, Prescilla Emy (Frontiers in Immunology, 2023)
The inflammasomes are intracellular multimeric protein complexes consisting of an innate immune sensor, the adapter protein ASC and the inflammatory caspases-1 and/or -11 and are important for the host defense against pathogens. Activaton of the receptor leads to formation of the inflammasomes and subsequent processing and activation of caspase-1 that cleaves the proinflammatory cytokines IL-1β and IL-18. Active caspase-1, and in some instances caspase-11, cleaves gasdermin D that translocates to the cell membrane where it forms pores resulting in the cell death program called pyroptosis. Inflammasomes can detect a range of microbial ligands through direct interaction or indirectly through diverse cellular processes including changes in ion fluxes, production of reactive oxygen species and disruption of various host cell functions. In this review, we will focus on the NLRP3, NLRP6, NLRC4 and AIM2 inflammasomes and how they are activated and regulated during infections with Gram-positive bacteria, including Staphylococcus spp., Streptococcus spp. and Listeria monocytogenes.